2023
DOI: 10.3390/ijms24054456
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Molecular Responses of Tomato to Prolonged and Short-Term Heat Exposure

Abstract: Tomatoes are one of the most important vegetables for human consumption. In the Mediterranean’s semi-arid and arid regions, where tomatoes are grown in the field, global average surface temperatures are predicted to increase. We investigated tomato seed germination at elevated temperatures and the impact of two different heat regimes on seedlings and adult plants. Selected exposures to 37 °C and heat waves at 45 °C mirrored frequent summer conditions in areas with a continental climate. Exposure to 37 °C or 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…In the same study, tomato seedlings aged 12 days (germination: 24 • C) were exposed to 37 • C for 24 h, and a 1 h heat wave (45 • C) damaged the seedling's recovery ability. Exposure to a 45 • C heat wave for 1 h, 3 h, 6 h, and 12 h showed that the seedlings started drying at 6 h and lost recovery capability at 12 h. The number of lateral roots was reduced, but the growth of the primary root was stopped at 37 • C. Although 45 • C did not affect lateral roots significantly, it halted the growth of the primary root [32,33]. High temperature reduces tomato root growth and nutrient uptake, affecting root-shoot source-sink relationships that affect fruit yield and quality [28,34].…”
Section: Introductionmentioning
confidence: 98%
“…In the same study, tomato seedlings aged 12 days (germination: 24 • C) were exposed to 37 • C for 24 h, and a 1 h heat wave (45 • C) damaged the seedling's recovery ability. Exposure to a 45 • C heat wave for 1 h, 3 h, 6 h, and 12 h showed that the seedlings started drying at 6 h and lost recovery capability at 12 h. The number of lateral roots was reduced, but the growth of the primary root was stopped at 37 • C. Although 45 • C did not affect lateral roots significantly, it halted the growth of the primary root [32,33]. High temperature reduces tomato root growth and nutrient uptake, affecting root-shoot source-sink relationships that affect fruit yield and quality [28,34].…”
Section: Introductionmentioning
confidence: 98%
“…Not all strategies used by plants to cope with stress are successful, and some symptoms, such as fruit weight reduction, seed abortion and reduced seed filling, may be observed (Martínez‐Lüscher et al., 2020; Swetha et al., 2021). Studies show that heat waves at temperatures of 37–45°C in the first 24 h are sufficient to generate deleterious effects on seeds (Martínez‐Lüscher et al., 2020; Swetha et al., 2021; Tokić et al., 2023). However, this condition may be related to the thermal tolerance of the species.…”
Section: Introductionmentioning
confidence: 99%